Dimensions of Artificial Intelligence and Data Strategies in Industrial Enterprises and Achieving Sustainable Leadership: A Reading in the Saudi Industrial National Strategy 2016-2030 - Benazza Hicham; Djilali Toumi Hamza (Journal of North African Economies, 2025)
It is very difficult to imagine an industry that will not be significantly impacted by data and artificial intelligence, contributing to enhancing economic performance, reducing costs, and improving operational efficiency. Artificial intelligence is expected to increase the global Gross Domestic Product (GDP) by approximately 14%, which is equivalent to around 58.9 trillion Saudi Riyals by 2030. It is anticipated that the Kingdom of Saudi Arabia will be a leader in the Middle East region in the artificial intelligence and big data market. Artificial intelligence plays a vital role in the future of the automation sector in the country. According to the Digital Riser 2020 report by the European Center for Digital Competitiveness, Saudi Arabia ranked first among the G20 countries. This substantial investment in artificial intelligence indicates that the contours of the industrial sector will change radically in the future. This study aims to elucidate the dimensions of artificial intelligence and data strategies in industrial enterprises and achieve sustainable leadership, with an analysis of the Saudi Industrial National Strategy 2016-2030.